Analisis Faktor-Faktor Yang Mempengaruhi Keterlambatan Pengobatan Pada Wanita Penderita Kanker Payudara Di Hospital Nasional Guido Valadares Dili Timor-Leste - Joaninha dos Reis da Costa; Domingos Soares; Marni -; Hermenegildo Herculano (STIKes Santa Elisabeth Medan, 2021)
Introduction : The management of breast cancer has progressed very rapidly, but the mortality rate and the incidence of breast cancer are still high because many breast cancer sufferers come to health services to get treatment when the disease is severe or at an advanced stage even though there is BSE (breast self-examination). for early detection. This study aims to determine the consequences, the factors that influence the delay in handling, complications, and the treatment process for breast cancer patients in the women's surgery room at HNGV. Method : Descriptive research, non-random sampling technique by accidental sampling with a sample of 15 people Result : The predisposing factor that affects the delay in treatment is the respondent's low education and the respondent does not have a family history of breast cancer so that the informant does not have experience and knowledge about breast cancer before. The respondent's attitude is less responsive to the disease, but when the respondent knows breast cancer, the respondent agrees to get treatment. The incubation period for breast cancer is long so that respondents do not know that they have breast cancer at stage III and when the respondent decides to seek treatment, the respondent is too late to get treatment. The enabling factors that influence the delay in treatment are the respondent's actions when they first find the disease, most of the respondents do not immediately treat the disease and do not go to the doctor after they find a lump in their breast and the respondent also prefers to seek treatment elsewhere. shaman with the belief that the healing will be faster even though the respondents have been diagnosed with breast cancer by the doctor Duscussion : Patients are often late in breast cancer treatment is influenced by the actions of respondents who prefer traditional treatment or to a traditional healer than a doctor. Reinforcing factor (reinforcing factor) does not affect the delay in treatment because the three components of this factor either family, friends or health workers strengthen the informant to immediately treat the disease. To the health office to provide counseling about breast cancer and the importance of doing BSE to all women of childbearing age (cancer age) to find breast cancer early so that sufferers can get treatment quickly and cooperate with the Da Saúde National Institute to provide counseling about breast cancer and BSE to women of childbearing age (cancer age). It is hoped that health workers at the Guido Valadares National Hospital to provide counseling about breast cancer and BSE to the families of female respondents.